The closer - Rivera, Mariano 1969- (Little, Brown and Company, 2014)
The nineteen-year veteran pitcher for the New York Yankees describes his life, discussing the difficulties in being a Latino baseball player in the U.S., how he keeps his Christian values in professional sports, and his championships and rivalries